PELAKSANAAN PERJANJIAN KERJA ANTARA KARYAWAN DENGAN PT. BAHARI SANDI PRATAMA PEKANBARU DIKAITKAN KINERJA KARYAWAN - Sulistiani Sulistiani; Zulfikar Jayakusuma; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
According to Law Number 13 of 2003 concerning Manpower contains the rights and obligations of workers. One of the obligations of workers contained in this Manpower Act, namely in Article 102 paragraph 2, the performance of workers is the obligation of workers after the company gives its rights to workers, PT. Bahari Sandi Pratama Pekanbaru is a sea transportation shipping company that has a target every year. The purpose of this study is to determine the implementation of work agreements between employees and PT. Bahari Sandi Pratama Pekanbaru is associated with employee performance. This type of research is classified in the type of sociological legal research, namely research on the effectiveness of existing law, the nature of this research is descriptive research that describes systematically, the facts and characteristics of the object under study appropriately. Research conducted at PT. Bahari Sandi Pratama Pekanbaru, while the population and sample are all parties involved in this study, both the chief financial officer and employees. Sources of data used are primary and secondary data, data collection techniques used by interviews, questionnaires and literature review. From the results of the research problem there are two main things that can be concluded, First, the implementation of the work agreement between the employee and PT. Bahari Sandi Pratama Pekanbaru was not carried out properly. Employees have defaulted by not carrying out what was promised. Secondly, internal factors, namely employees themselves, excessive workloads which lead to concurrent positions and multiple duties and the lack of strict application of sanctions from the company itself, listen to external factors namely a less comfortable work environment that does not increase employee performance. The author's suggestion, First, should the parties in the work agreement must fulfill what is their rights and obligations as agreed between the employee and PT. Bahari Sandi Pratama Pekanbaru. Second, to minimize the causes of employees not improving performance at PT. Bahari Sandi Pratama Pekanbaru should the parties be able to pursue all rights and obligations properly for the good of both parties Keywords: work agreements, performance, employees, employer.